Characterizing socially avoidant and affiliative responses to social exclusion - Powers, Katherine E.; Heatherton, Todd F. (Frontiers in Integrative Neuroscience, 2012)
Humans have a fundamental need for social relationships. From an evolutionary standpoint, the drive to form social connections may have evolved as an adaptive mechanism to promote survival, as group membership afforded the benefits of shared resources and security. Thus, rejection from social groups is especially detrimental, rendering the ability to detect threats to social relationships and respond in adaptive ways critical. Previous research indicates that social exclusion alters cognition and behavior in specific ways that may initially appear contradictory. That is, although some studies have found that exclusionary social threats lead to withdrawal from the surrounding social world, other studies indicate that social exclusion motivates affiliative social behavior. Here, we review the existing evidence supporting accounts of avoidant and affiliative responses, and highlight the conditions under which both categories of responses may be simultaneously employed. Then, we review the neuroimaging research implicating specific brain regions underlying the ability to detect and adaptively respond to threats of social exclusion. Collectively, these findings are suggestive of neural system highly attuned to social context and capable of motivating flexible behavioral responses.